MicroRNA-1 Negatively Regulates Peripheral NK Cell Function via Tumor Necrosis Factor-Like Weak Inducer of Apoptosis (TWEAK) Signaling Pathways During PPRV Infection - Qi, Xuefeng; Li, Zhen; Li, Huan; Wang, Ting; Zhang, Yanming; Wang, Jingyu (Frontiers in Immunology, 2020)
Peste des petits ruminants virus (PPRV) is an important pathogen that seriously influences the productivity of small ruminants worldwide. PPRV is lymphotropic in nature and induce in the hosts a transient but severe immunosuppression, especially innate immunity. However, it remains largely unknown how NK cells respond and are regulated at the earliest time points after an acute viral PPRV infection in goats. In this study, we revealed multiple immune responses of goat peripheral NK cells were compromised during PPRV infection, including the cytolytic effector molecules expression and cytokines production. Importantly, we demonstrated that increased TWEAK expression in PPRV infected goat NK cells suppressed cytotoxicity as well as cytokine production, and TWEAK acting as a negative regulator in NK cells during PPRV infection. Furthermore, we found that PPRV infection induced TWEAK expression in goat NK cells involving post-transcriptional by suppressing miR-1, a novel negative miRNA directly targeting TWEAK gene. Furthermore, replication of virus is required for inhibition of miR-1 expression during PPRV infection, and non-structural V protein of PPRV plays an important role in miR-1 mediated TWEAK up regulation. Moreover, we revealed that the regulation of NK cells immune responses by TWEAK is mediated by MyD88, SOCS1, and STAT3. Taken together, our results suggest a previously unrecognized role for TWEAK on the regulation of goat peripheral NK cells cytotoxicity and cytokines expression during PPRV infection.